Implementasi Strategi Pembelajaran Berdiferensiasi Dalam Materi Teks Berita Pada Siswa Kelas VII H SMP Negeri 13 Surabaya - Rizky Ananda Putri Wicaksono; Sueb Hadi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Effective education requires an approach that meets the needs of diverse students. Differentiated learning strategy is one of the methods that can accommodate students' different abilities, interests and learning styles. This study aims to assess the effectiveness of differentiated learning strategies in improving students' understanding of news text material, as well as analyzing the impact of these strategies on students' involvement and participation during the teaching and learning process. The method used in this research is Classroom Action Research (PTK) with Kemmis & McTaggart model, which involves cycles of planning, action, observation, and reflection. The research findings showed an increase in student learning outcomes as well as an increase in student engagement and participation in the classroom. The implication of this research shows that the application of differentiated learning strategies can significantly improve material understanding and student engagement, so it can be an effective strategy to be applied in the learning process in the classroom to meet diverse learning needs.